PENERAPAN PARENTING PADA PERKEMBANGAN ANAK USIA DINI MENURUT SUDUT PANDANG ISLAM - Denny Erica (Universitas Bina Sarana Informatika, 2016)
At an early age a child will need a lot of attention and affection from bothparents. Psychologically figure of a father and mother will greatly Affect thebehavior and thinking patterns of a child. Every time a child will be using one ofthe senses as a form of stimulus for the establishment of relations of innervation(synapses) are Carried out repeatedly so that it Becomes a record of experiencein Determining how children in thinking, feeling, behavior, and learning in thepresent and future. Synapses that are not getting the Necessary stimulus willdisappear and a process of elimination of nerve connections are redundant andnot Necessary (synaptic pruning).With the application of the parents' parenting (parenting) Islamically, isexpected to a make early childhood can undergo periods of adapting a much morefocused, that Eventually the children had kharakter and a strong faith inundergoing the process of a child's growth.